Kesesuaian Penempatan Kerja dan Kompetensi terhadap Prestasi Kerja yang Dimoderasi oleh Tingkat Pendidikan pada Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Shahnaz Nabila; Bagus Handoko; M. Fauzan Azhmy (Universitas Bumigora, 2021)
This study aims to determine the effect of suitability of work placement and compensation on work performance in the Medan City Regional Tax and Retribution Management Agency. To find out whether the level of education moderates the effect of suitability of work placement and competence on work performance in the Medan City Regional Tax and Retribution Management Agency. The population in this study was 175 people, and using slovin obtained a sample of 121 people. The analysis technique used is multiple linear regression and MRA. The results showed that the suitability of work placement had a significant effect on job performance in the Medan City Regional Tax and Retribution Management Agency. Competence does not affect work performance at the Medan City Regional Tax and Retribution Management Agency. The conclusion that can be obtained from the above results is that the moderator is proven to be significant in influencing the suitability of work placement for work performance. The conclusion that can be obtained from the above results is that the moderator is proven to be significant in influencing competence on work performance.